Interleukin-18 and CD30 serum levels in patients with moderate-severe depression - Rosaria Alba Merendino; Antonio Enrico Di Rosa; Giuseppe Di Pasquale; Paola Lucia Minciullo; Carmela Mangraviti; Antonella Costantino; Antonella Ruello; Sebastiano Gangemi (Hindawi Limited, 2002)
Interleukin-18 (IL-18), a pro-inflammatory cytokine that plays an important role in the T-cell-helper type 1 response, is a new member of the family of cytokines produced in the brain. CD30 is a marker of T-cell-helper type 2 lymphocytes. We evaluated IL-18 and CD30 serum levels in 10 patients affected by moderate-severe depression (MSD). We demonstrated for the first time that serum IL-18 levels of MSD patients were significantly higher than those of healthy donors. On the contrary, no significant difference was found between serum CD30 levels of MSD patients compared with those of healthy donors. These data strengthen the hypothesis that MSD disease is associated with an inflammatory response, mainly T-cell-helper type 1, and suggest an important role for IL-18 in the pathophysiology of MSD.